2011
DOI: 10.1007/s10658-011-9833-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling of watermelon during its incompatible interaction with Fusarium oxysporum f. sp. niveum

Abstract: Transcriptome profiling of watermelon during its incompatible interactions with Fusarium oxysporum f.sp. niveum (FON) was performed using an Agilent custom microarray, which contains 15,000 probes representing approximately 8,200 watermelon genes. A total of 24, 275, 596, 598, and 592 genes showed significant differential expression in FONinfected plant roots, as compared with mockinoculated roots, at 0.5, 1, 3, 5 and 8 days post inoculation (dpi), respectively. Bioinformatics analysis of these differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 33 publications
3
34
1
Order By: Relevance
“…Further analysis showed that the transcription levels of GST, CCoAM and CAD in the highly resistant cultivar were higher than those in the susceptible cultivar, which is in agreement with previous observation in watermelon challenged with Fusarium oxysporum f. sp. Niveum [59]. These results indicated that full lignification is likely to contribute to disease resistance.…”
Section: Discussionmentioning
confidence: 75%
“…Further analysis showed that the transcription levels of GST, CCoAM and CAD in the highly resistant cultivar were higher than those in the susceptible cultivar, which is in agreement with previous observation in watermelon challenged with Fusarium oxysporum f. sp. Niveum [59]. These results indicated that full lignification is likely to contribute to disease resistance.…”
Section: Discussionmentioning
confidence: 75%
“…Lü et al [29] demonstrated that JA biosynthesis and shikimate-phenylpropanoid-lignin pathways are important processes in watermelon resistance against Fon infection. We found in this study, expression levels of the genes in responsible for biosynthesis of JA and shikimate-phenylpropanoidlignin were enhanced in both monoculture and companion cropping with Fon inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…As the control, watermelon monoculture, each pot contained one watermelon seedling. The seedlings were watered every two days with Hoagland nutrient solution throughout the experiments [29]. Peat soil and vermiculite moisture levels were maintained by weighing irrigation manually.…”
Section: Inoculation Experimentsmentioning
confidence: 99%
See 2 more Smart Citations